(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the prevalence of the decline in daily functioning and to identify associated factors among older adult patients with diabetes hospitalized at Hue University of Medicine and Pharmacy Hospital. Subject and methods: A cross - sectional study was conducted on 217 older adult patients with diabetes at Hue University of Medicine and Pharmacy Hospital. Results: 13.4% of participants experienced a decline in activity daily living (ADL) and 59 % showed a decline in instrument activity dailly living (IADL). Age, occupation, and physical activity were statistically significant factors associated with the decline in ADL. Additionally, there were statistically significant associations between age, occupation, marital status, fasting blood glucose levels, physical activity, and the decline in IADL. Conclusion: The prevalence of the decline in daily functioning among older adults with diabetes is relatively high. Therefore, nurses should develop comprehensive assessment plans to help reduce the risk of further functional decline.